2016
DOI: 10.1007/s11136-016-1381-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of health-related quality of life and association with survival may identify colorectal cancer patients at high risk of poor prognosis

Abstract: Purpose To investigate the mediators of health-related quality of life (HR-QoL) in colorectal cancer (CRC) patients and effect on overall survival. Methods We analyzed baseline (within 1 year of diagnosis) SF-12v1 questionnaire data from 3,734 CRC patients and assessed the differences in mental composite scores (MCS) and physical composite scores (PCS) by socio-demographics and risks of poor HR-QoL by these factors. Hazard ratios were generated using univariate cox regression for MCS and PCS dichotomized usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…[170] One might then question whether the term QoL is used correctly in this thesis, even though the SF-12 has been used in other studies to assess HRQoL in CRC patients. [144,164,181] Another limitation is that we scored the PCS and MCS subscales using the 1998 U.S.…”
Section: Measuring Qol Using the Sf-12mentioning
confidence: 99%
See 1 more Smart Citation
“…[170] One might then question whether the term QoL is used correctly in this thesis, even though the SF-12 has been used in other studies to assess HRQoL in CRC patients. [144,164,181] Another limitation is that we scored the PCS and MCS subscales using the 1998 U.S.…”
Section: Measuring Qol Using the Sf-12mentioning
confidence: 99%
“…[224] Given the lack of a standardized tool, other PROMs used in studies of CRC patients include the EORTC QoL questionnaires, [143,148,211,225,226] the MSAS, [66,105,200] and SF-12. [144,164,227] However, the use of PROMs in the clinical setting is not useful without follow-up strategies. It is important to use methods that can ensure an easy and quick response to, and management of, symptoms, [14] to allow both patients and their caregivers access to the results.…”
Section: Self-report In the Clinical Settingmentioning
confidence: 99%
“…There is evidence that older age has negative effects on the QoL in cancer patients [ 5 , 6 ], while gender has an influence on the degree of QoL impairment [ 7 ]. Lack of education has a negative effect on cancer patients [ 7 ], and low income has also been negatively associated with QoL in cancer patients [ 8 11 ]. Other factors contributing to QoL impairment may include clinical presentations of cancer patients such as the stage, type, and site of the cancer [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…He illustrated that patients' global health, QOL, EF, and physical function begin to improve in the third month, and that it takes 2 years for the nausea and vomiting, agrypnia, constipation, and diarrhea scores to revert to baseline values. Reyes et al [22] found significant differences in health-related quality of life (HR-QOL) among racial groups, with African-Americans showing the worst HR-QOL, which was measured using physical and mental composite scores. Our study demonstrated that there was no significant difference in sex, age, preoperative CRP levels, maximum tumor diameter, bowel resection length, TNM stage, tumor differentiation, and chemotherapy between the two groups, although surgical method, TD, and AD differed.…”
Section: Discussionmentioning
confidence: 99%